The role of political parties in Egypt (1978-2017) and the resilience of authoritarianism - Shaheen, Yasmeen (AUC Knowledge Fountain, 2019)
The current thesis focuses on the immense importance of the role of political parties in Egyptian politics and the Resilience of Authoritarianism, tracing their evolution and development from 1978 to 2017. It has proved that Egyptian political parties, in the period of the present work, have failed to consolidate democratic transformation by institutionalizing authoritarianism. This role has been so marginal that these pre- and post-Uprising political parties have been ridiculed as Ahzab Cartooniyah (Cardboard Parties). It has been found that about 100 parties out of 109 are remarkably so feeble and even paralyzed in their opposition to autocratic and dictatorial practices. Therefore, these political parties are incapable of supporting democratization. It has focused on the role of political parties in authoritarian regimes under which they further support authoritarianism. Moreover, it has analyzed the role of political parties in public mobilization as well as the variances in their organizational structures, mobilization and institutional potentials, and popular bases. The thesis has adopted the "semi-structured interviews, as a qualitative interpretive methodology, with the parties' leaders, chief members, and cadres (medium level and grassroots)". It also employs the authoritarian resilience theory for conducting this research and the comparative historical institutional approach while examining the authoritarian resilience theory to account for the failure of Egyptian political parties in democracy promotion.